2018
DOI: 10.1101/284034
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures reveal opening of the store-operated calcium channel Orai

Abstract: The store-operated calcium (Ca 2+ ) channel Orai governs Ca 2+ influx through the plasma membrane of many non-excitable cells in metazoans. The channel opens in response to depletion of Ca 2+ within the endoplasmic reticulum (ER). Loss-and gain-of-function mutants of Orai cause disease. Our previous work revealed the structure of Orai with a closed pore. Here, using a gain-of-function mutation that constitutively activates the channel, we present an X-ray structure of Drosophila melanogaster Orai in an open co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(74 citation statements)
references
References 65 publications
6
66
0
2
Order By: Relevance
“…This conclusion agrees with studies on cross-linking of the M4-ext helices by Tirado-Lee et al (27). Recent structural analysis has suggested that the interacting pairs of M4-ext helices act as latches on the outside of the channel that must be opened to allow the M1-ext helices to expand outward thus permitting the cytosolic mouth of the pore to open (36). This model was based on a crystallized dOrai structure that stabilized the unlatched channel with straightened M4-ext helices.…”
Section: Function Of Orai1 Dimerssupporting
confidence: 91%
See 2 more Smart Citations
“…This conclusion agrees with studies on cross-linking of the M4-ext helices by Tirado-Lee et al (27). Recent structural analysis has suggested that the interacting pairs of M4-ext helices act as latches on the outside of the channel that must be opened to allow the M1-ext helices to expand outward thus permitting the cytosolic mouth of the pore to open (36). This model was based on a crystallized dOrai structure that stabilized the unlatched channel with straightened M4-ext helices.…”
Section: Function Of Orai1 Dimerssupporting
confidence: 91%
“…First, our studies provide some important new understanding on the properties of the pore-selectivity filter that normally functions with six charged Glu residues. We speculate that these residues may have sufficient flexibility to allow formation of two Ca 2ϩ -binding sites within the selectivity filter, as suggested recently (36). The symmetrical and somewhat conservative replacement of three Glu residues with three intervening Gln residues (formed with OQ or QO dimers) may prevent formation of the putative second site and render the pore as a nonselective cation channel.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…We illustrate the effectiveness of this heuristic approach using two recent structures ( Fig. 6): one of the TRPV3 channel in a putative sensitised (but non-conductive) conformation (PDB ID: 6MHS) and one of the CRAC channel (Orai) in an open conformation (PDB ID: 6BBF) (35). For the openstate Orai channel, none of the (hydrophobicity, radius) points fall below the SVM classification line and so the structure is predicted to be fully wetted and correspond to a functionally open state of the channel.…”
Section: A Heuristic For Predicting the Conductive Statementioning
confidence: 99%
“…The consequent reduction of ER Ca 2+ is sensed by the ER-resident membrane 75 protein Stim1 (Hogan and Rao, 2015), resulting in its interaction with Orai1 at PM-ER contact sites, 76 CRAC channel opening, and the influx of extracellular Ca 2+ . Channel opening relies both on Orai1 77 multimerisation into a pore-forming hexameric unit, and a concerted set of conformational changes 78 (Hou et al, 2012;Cai et al, 2016;Hou et al, 2018). The main interaction with the cytoplasmic 79 domain of Stim1 occurs via the C-terminal cytoplasmic domain of Orai1, which is anchored to the 80 membrane by its fourth transmembrane domain (TMD) (Park et al, 2009).…”
mentioning
confidence: 99%